Administering oral, topical, suppository and inhalant medications - Sicking, Janet; Harvey, Lori; Voorhees, Marguerite T.; Medcom, inc. (Cypress, CA : Medcom Trainex, 2003)
(Producer) Prerequisite knowledge and skills for administrating oral, topical, suppository, and inhalant medications are presented in this program which has also been updated to reflect current hand hygiene technique. Oral medications are introduced first beginning with types of solid and liquid forms.Guidelines for preparing oral medications are demonstrated including administration via a nasogastric tube and sublingual administration. Different forms of topical medications and techniques for application of topical discs, sterile ophthalmic ointments and drops, and nasal agents are shown. The suppository method of administration is presented with emphasis given to techniques for rectal and vaginal administration. Devices used to administer prescribed inhalant medication are introduced and skills for their use are demonstrated for patient teaching
Consultants, Jan Sicking, Lori Harvey, Marguerite T. Voorhees
VHS
Keywords: Pharmaceutical Preparations -- administration & dosage -- Nurses' Instruction; Drug Administration Routes -- Nurses' Instruction